2006
DOI: 10.1093/ije/dyl176
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of retrospective and prospective occurrences in cohort studies: HIV-1 serostatus and incident pneumonia

Abstract: As expected, HIV-1 infection increases the hazard of pneumonia, with more precise inference obtained by combining information available on bidirectional occurrences. The proposed method for the analysis of bidirectional occurrence times will improve precision when the estimated associations are homogeneous across occurrence types, or may provide added insight into either the data collection or disease process when the estimated associations are heterogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Separate models were constructed for retrospectively-reported TTP only and retrospectively-reported with prospectively observed TTP; all adjusted for age, BMI, and smoking at each attempt. When including both retrospectively-reported and prospectively observed TTPs, models included a strata statement for TTP type and a TTP type*BMI interaction term (17). A bootstrap approach was used to test difference in frailty variances between models based on overlapping subgroups of women.…”
Section: Methodsmentioning
confidence: 99%
“…Separate models were constructed for retrospectively-reported TTP only and retrospectively-reported with prospectively observed TTP; all adjusted for age, BMI, and smoking at each attempt. When including both retrospectively-reported and prospectively observed TTPs, models included a strata statement for TTP type and a TTP type*BMI interaction term (17). A bootstrap approach was used to test difference in frailty variances between models based on overlapping subgroups of women.…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies have found that this method of analysis did not affect the results and may in fact improve the clarity of the final outcome. 8,38 The lack of validation of our 6-point scale is also a weakness, although a significant correlation did occur with the Tegner (r = 0.955; P \ .001) and the 111-Level sport scale (r = -0.617; P \ .001).…”
Section: Strengths and Weaknessesmentioning
confidence: 92%
“…Prospective surveillance data from sub-Saharan Africa and high-income countries consistently show a higher incidence of severe all-cause acute RTI or pneumonia in HIV-infected compared with uninfected adults and children. [11][12][13][14][15] Risk factors for RTIs among HIV-infected individuals include increasing age, greater immunosuppression, recurrent pneumonia, and cigarette smoking. 16 In LMIC, these risks are compounded by other factors such as poor hygiene, and unreliable water supplies.…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%